2002
DOI: 10.3171/jns.2002.97.1.0065
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery providing long-term tumor control of cavernous sinus meningiomas

Abstract: Stereotactic radiosurgery provided safe and effective management of cavernous sinus meningiomas. We believe it is the preferred management strategy for tumors of suitable volume (average tumor diameter < or = 3 cm or volume < or = 15 cm3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(196 citation statements)
references
References 41 publications
12
176
0
8
Order By: Relevance
“…After 1 year and 5 years, the rate for radiation-related complications were 6% and 11%, respectively. Other authors reported comparable results [11,12,32]. SRS is therefore commonly used for small lesions ( < 3 cm) while larger lesions, and lesions with a close proximity to the brain stem or other organs at risk, are treated by fractionated stereotactic radiotherapy.…”
Section: Skull Base Tumorssupporting
confidence: 49%
“…After 1 year and 5 years, the rate for radiation-related complications were 6% and 11%, respectively. Other authors reported comparable results [11,12,32]. SRS is therefore commonly used for small lesions ( < 3 cm) while larger lesions, and lesions with a close proximity to the brain stem or other organs at risk, are treated by fractionated stereotactic radiotherapy.…”
Section: Skull Base Tumorssupporting
confidence: 49%
“…Actual tumor growth control rate after GMK of CS meningiomas ranged from 91% to 96.5% at 5 years and 82% to 94% at 10 years (10,12,13,16,23,24,35). In our series, 85.7% patients (12 out of 14 patients) after GMK treatment did not regrow for a mean follow up of 90.6 months and 2 patients had related acceptable complications, including 1 patient had visual deterioration and 1 face hypesthesia on the side of tumor after GMK.…”
Section: Radiosurgerymentioning
confidence: 81%
“…If the tumour is densely adherent to vital blood vessels, nerves or the brainstem and hard to resect completely, it is considered optimal to leave a small margin of tumour behind and implement postoperative adjuvant radiotherapy or γ-knife therapy to control tumour recurrence effectively. 21,22 The primary objective in resecting posterior petrous meningiomas is to remove the tumour base to stop the blood supply and reduce haemorrhage. Sometimes, because of the large size of these tumours and the complicated associations that they make with the surrounding anatomical structures, it is not easy to separate the tumour base until internal decompression has been performed repeatedly and the tumour resected little by little.…”
Section: Discussionmentioning
confidence: 99%